2020
DOI: 10.1016/j.cub.2020.01.079
|View full text |Cite
|
Sign up to set email alerts
|

Crossover Position Drives Chromosome Remodeling for Accurate Meiotic Chromosome Segregation

Abstract: Highlights d CO position affects the formation of chromosome subdomains d COs at the center of autosomes lead to premature loss of sister chromatid cohesion d The CO-unfavorable center region encompasses up to 6% of the total chromosome length d CO formation close to telomeres is highly suppressed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…Moreover, a recent C . elegans study has found that the asymmentric placement of the crossover along the chromosome is important for proper chromosome remodeling and segregation [ 42 ]. Perhaps the acquisition of holocentric chromosomes requires extreme crossover interference in addition to asymmetric placement of a crossover along the chromosome length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a recent C . elegans study has found that the asymmentric placement of the crossover along the chromosome is important for proper chromosome remodeling and segregation [ 42 ]. Perhaps the acquisition of holocentric chromosomes requires extreme crossover interference in addition to asymmetric placement of a crossover along the chromosome length.…”
Section: Discussionmentioning
confidence: 99%
“…One way that C. elegans counteract this problem is the asymmetric positioning of a single crossover along the length of a chromosome; this generates a single point of organization along the length of each chromosome, which patterns the chromosome in a manner that facilitates chromosome biorientation, alignment, release of cohesion, and segregation [40,41]. Moreover, a recent C. elegans study has found that the asymmentric placement of the crossover along the chromosome is important for proper chromosome remodeling and segregation [42]. Perhaps the acquisition of holocentric chromosomes requires extreme crossover interference in addition to asymmetric placement of a crossover along the chromosome length.…”
Section: Crossover Interference and Holocentric Chromosomesmentioning
confidence: 99%
“…In the holocentric C. elegans, a single crossing-over event partitions the chromosome into the short and long arms and distributes key chromosome-associated proteins asymmetrically relative to the crossover site, eventually defining where cohesion will be released during meiosis I ( Altendorfer et al, 2020 ; Martinez-Perez et al, 2008 ; Nabeshima et al, 2005 ). While two axis components, HTP-3 and HIM-3, remain associated with all arms of chromosomes ( Zetka et al, 1999 ; Goodyer et al, 2008 ; Severson et al, 2009 ), the other axis-associated proteins, HTP-1/2 and LAB-1, become restricted to the long arm of a bivalent ( de Carvalho et al, 2008 ; Martinez-Perez et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meiotic recombination, which is necessary for proper chromosomal segregation, is tightly regulated by the intricate integration of programmed DSB induction, HR repair machinery and chromosomal remodelling resulting in the right proportions of CO and NCO recombinants ( Altendorfer et al, 2020 ). The frequency and distribution of COs are regulated by the still poorly understood phenomena of CO homeostasis and interference, respectively ( Wang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%